The Role of Biometric Technology to Protect Consumer in Online Banking Transaction - et al., Edy Santoso (International Journal of Advanced Science and Technology, 2019)
The development of information technology (IT) in online banking model provides an efficiency and effectively for account holder to conduct online transaction. In this situation, technology and financial services law plays an important role in providing protection of financial identity. Nowadays, the most of online banks offer transaction safety when consumer access to login page of websites to warn users about the existence of such scams. However, the cases of online banking scams have been increasing from time to time. Perpetrator can access to the consumer’s account and do online transaction illegally. Identity theft is one of the fastest growing types of consumer fraud. In this regards, using biometric technology, such as fingerprint technology is very important to protect the consumer identity during online transaction in over the world. It is a form of innovation technology through biometric technology can be used for real evidence in law enforcement at cyberspace. This paper uses qualitative empirical legal research with multidisciplinary research approach through the analysis of legal rules under Indonesian Law on Information and Transaction Electronic. The objective of this paper is examined consumer identity theft protection in online banking transaction through biometric technology application. This paper identified that banking security through biometric application is very important. The biometrics technology can be applied for e-verification as real evidence in detecting authorized user.  It will support banking security as an effort for consumer protection.